Diversified Business Groups and Corporate Refocusing in Emerging Economies - Hoskisson, Robert E.; Johnson, Richard A.; Tihanyi, Laszlo; White, Robert E. (Journal of Management, 2005)
As emerging economies have improved their economic institutions, the performance of many large business groups has been reduced because such groups acted as market-substitute mechanisms. Consequently, business groups have become increasingly involved in refocusing activities. The authors develop a framework in which such refocusing is explained as an attempt to balance overall transaction costs faced by groups with organization-specific costs in order to improve group performance. They examine external and internal factors that might lead to the initiation of refocusing and also explain why different ownership structures may affect the direction of that refocusing (e.g., related vs. unrelated diversification).